2022
DOI: 10.1109/tcyb.2017.2662199
|View full text |Cite
|
Sign up to set email alerts
|

Deep Pain: Exploiting Long Short-Term Memory Networks for Facial Expression Classification

Abstract: This article has been accepted for inclusion in a future issue of this journal. Content is final as presented, with the exception of pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 63 publications
2
153
2
Order By: Relevance
“…The latter layers of the convoluted neural network are typically a number of fully connected layers and a classifier. In recent years, convolution neural networks have been successfully applied to facial expression recognition [30, 31], face recognition [32, 33], human posture estimation [34], age estimation [35, 36], and speech recognition [37, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…The latter layers of the convoluted neural network are typically a number of fully connected layers and a classifier. In recent years, convolution neural networks have been successfully applied to facial expression recognition [30, 31], face recognition [32, 33], human posture estimation [34], age estimation [35, 36], and speech recognition [37, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…The landmark-based approaches quantify facial movements using key facial points applying the sequence of face detection 25,115 and facial landmarks estimation. 117,118 These proposals have demonstrated that the most important advantage of deep learning is that the learned dynamic appearance or discriminative features of facial expressions could be generalized and applied to different datasets and applications. On the other hand, the region-based methods process the raw sequence of images through an end-to-end deep learning model to learn the spatiotemporal features.…”
Section: Human Motion Analysis and Deep Learningmentioning
confidence: 99%
“…On the other hand, the region-based methods process the raw sequence of images through an end-to-end deep learning model to learn the spatiotemporal features. 117,118 These proposals have demonstrated that the most important advantage of deep learning is that the learned dynamic appearance or discriminative features of facial expressions could be generalized and applied to different datasets and applications.…”
Section: Human Motion Analysis and Deep Learningmentioning
confidence: 99%
“…The prediction for each of these modalities was obtained using binary classifiers (e.g., SVM) trained using handcrafted features. Recently, deep learning methods [15], [16] have become popular in pain classification. In case of infants, Celona and Manoni [17] proposed a framework that combines both handcrafted and deep features for classifying COPE images as pain/no-pain.…”
Section: Introductionmentioning
confidence: 99%